STRATEGI PEMASARAN DALAM PERSAINGAN DESTINASI PARIWISATA - Suhartapa Suhartapa (Pringgitan, 2021)
Tourism destination marketing activities begin by selecting target markets, and these activities are referred to as the segmenting and targeting process. Meanwhile, activities to acquire, maintain and develop target markets are called the selling process. And the last thing is creating, delivering and communicating the destination offering is called the positioning process. The process of tourism activities can be in the form of long-term decisions or strategic levels which include the branding, segmenting, targeting, selling and positioning processes. Meanwhile, the short-term activity process or the tactical level is usually called a marketing program in the form of various maneuvers so that the predetermined marketing strategy can run well. Meanwhile, tactical activities, which are usually called marketing programs, are short-term processes aimed at making the marketing strategy run as determined. Activities that are tactical in this marketing program are decisions about the marketing mix. Competition for tourism destinations can be carried out through strategies that optimize the functions of tourism destinations. Like other industries, the function of a tourism destination can be in the form of an operational function and a marketing function.Keywords: Marketing Strategy, Competitive Strategy, Tourism Destination